(untitled) (IJOVTECH, 2026)
The challenges that have persistently inhibited the economic growth and services in the developing region, in this case Ebonyi State, Nigeria, include the corruption, inefficiency and lack of transparency in the public procurement management. This paper considers the possibilities of new technologies such as e-procurement systems, artificial intelligence, blockchain, and data analytics as ways to improve the efficiency of overseeing the processes of public procurement. Using the mixed-methodology, the primary data were gathered via surveys and interviews conducted with 150 procurement officials and Ebonyi State stakeholders using secondary data sources both past and present. The theoretical framework will use the Technology-Organization-Environment (TOE) model in examining factors of adoption. The results indicate that the awareness of technologies is average (58% of the participants knew about e-procurement) but the adoption is limited by the infrastructural shortage, change unwillingness, and level of regulation. Demographic analysis indicates that the respondents are mainly male (72%), between 35-50 years (65%), and possess bachelor degrees (48%) and 5-15 years experience (62). Findings show that the adoption of e-procurement has the potential of saving procurement cycle times by up to 40 per cent and eliminate corruption by conducting bidding in an open way. The analysis has provided advantages such as cost reductions and enhanced accountability but has emphasized such limiters as digital divide, and lack of skills. Some of the recommendations include technology integration, capacity building and public-private partnerships policy reforms. The study is relevant in the literature of business management in offering empirical findings on technology mediated procurement reforms in sub-Saharan Africa with focus on sustainable development goals. Research needs to be carried out on long term effects after adoption.